Physical therapy consultation in the emergency department for older adults with falls: A qualitative study - Anita Chary; Elise Brickhouse; Beatrice Torres; Lauren Cameron‐Comasco; Sangil Lee; Brittany Punches; Rachel M. Skains; Aanand D. Naik; Catherine C. Quatman‐Yates; Maura Kennedy; Lauren T. Southerland; Shan Liu (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Little is known about current practices in consulting physical therapy (PT) in the emergency department (ED) for older adults with falls, a practice that can reduce fall‐related ED revisits. This qualitative study aimed to understand perspectives of ED staff about ED PT consultation for older adults with falls and fall‐related complaints, specifically regarding perceived value and associated challenges and strategies. Methods We performed focus groups and key informant interviews with emergency physicians, advanced practice clinicians, nurses, physical therapists, occupational therapists, and technicians who perform ED geriatric screenings. We used rapid qualitative analysis to identify common themes related to decisions to consult PT from the ED, perceived value of PT, and common challenges and strategies in ED PT consultation. Results Twenty‐five participants in 4 focus groups and 3 interviews represented 22 distinct institutions with ED PT consultation available for older adults with falls. About two thirds of EDs represented relied on clinician gestalt to request PT consultation (n = 15, 68%), whereas one third used formal consultation pathways (n = 7, 32%). Participants valued physical therapists’ expertise, time, and facilitation of hospital throughput by developing safe discharge plans and contact with patients to improve outpatient follow‐up. Common challenges included limited ED PT staffing and space for PT evaluations; strategies to promote ED PT consultation included advocating for leadership buy‐in and using ED observation units to monitor patients and avoid admission until PT consultation was available. Conclusion ED PT consultation for older adults with falls may benefit patients, ED staff, and hospital throughput. Uncertainty remains over whether geriatric screening‐triggered consultation versus emergency clinician gestalt successfully identifies patients likeliest to benefit from ED PT evaluation. Leadership buy‐in, designated consultation space, and formalized consultation pathways are strategies to address current challenges in ED PT consultation.